Ekologi Sosial Baru Pengelolaan Limbah Rumah Tangga Menggunakan Maggot di Dusun Winong - Ayni, Jariah Sinta; A Zahid, A Zahid; Farihin, Zainul (Dharmahita: Journal of Community Service and Development, 2025)
This community empowerment research examines the use of Maggots as an alternative medium to reduce organic waste on a household scale in Winong Hamlet, Sendang District, Tulungagung Regency. Maggots were chosen as an alternative that the community can do because their cultivation is relatively easy. The purpose of this empowerment initiative is to optimize the use of organic waste in households, thereby reducing organic waste in the Winong Hamlet area while increasing its value. The SLA (Sustainable Livelihood Assessment) method is used to facilitate empowerment activities. This study employs social ecology theory to offer significant implications for environmental conservation efforts aimed at achieving ecological resilience. The results of this empowerment show that the community in Winong Hamlet can accept the understanding about reducing household waste. Maggots are an opportunity to reduce organic waste produced from each household, efficiency is felt for the community who cultivate maggots starting from poultry feed because of its high protein content, fish feed, and can fertilize the planting medium, however, the obstacle felt is the selection of land that is quite far from residents because it produces an unpleasant odor.